GB-to-TNT: Facilitating creation of matrices from GenBank and diagnosis of results in TNT - Goloboff, Pablo Augusto (2012)
This paper presents a pipeline, implemented in an open-source program called GB→TNT (GenBank-to-TNT), for creating large molecular matrices, starting from GenBank files and finishing with TNT matrices which incorporate taxonomic information in the terminal names. GB→TNT is designed to retrieve a defined genomic region from a bulk of sequences included in a GenBank file. The user defines the genomic region to be retrieved and several filters (genome, length of the sequence, taxonomic group, etc.); each genomic region represents a different data block in the final TNT matrix. GB→TNT first generates Fasta files from the input GenBank files, then creates an alignment for each of those (by calling an alignment program), and finally merges all the aligned files into a single TNT matrix. The new version of TNT can make use of the taxonomic information contained in the terminal names, allowing easy diagnosis of results, evaluation of fit between the trees and the taxonomy, and automatic labelling or colouring of tree branches with the taxonomic groups they represent. © The Willi Hennig Society 2012.